1991
DOI: 10.1182/blood.v78.10.2520.bloodjournal78102520
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of two different doses of cytarabine for acute myeloid leukemia: a phase III trial of Cancer and Leukemia Group B

Abstract: Between 1982 and 1986, 326 evaluable patients with acute myeloid leukemia (AML) were randomized to receive cytarabine (Ara-C) at 200 mg/m2 (A200) or 100 mg/m2 (A100) for induction and maintenance therapy. Cycle 1 of induction therapy consisted of 7 days of continuous intravenous (IV) Ara-C and 3 days of i.v. daunorubicin (DNR); cycle 2, if needed, consisted of 5 days of Ara-C and 2 days of DNR. Complete responders (CR) then received monthly subcutaneous (SC) Ara-C at the respective doses (A100 or A200) with 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Similar toxicities were also observed in a phase III clinical trial at low dose (100 mg/m 2 ) and high dose (200 mg/m 2 ) of Cytosar-U. [111] This study was able to conclude that high-dose regimen used did not have a significant difference in overall survival or duration of relapse-free survival compared with the low-dose regimen. A similar study compared two induction regimens in 860 patients between the ages of 16 and 60 years.…”
Section: Meretrix Meretrix Linnaeussupporting
confidence: 78%
“…Similar toxicities were also observed in a phase III clinical trial at low dose (100 mg/m 2 ) and high dose (200 mg/m 2 ) of Cytosar-U. [111] This study was able to conclude that high-dose regimen used did not have a significant difference in overall survival or duration of relapse-free survival compared with the low-dose regimen. A similar study compared two induction regimens in 860 patients between the ages of 16 and 60 years.…”
Section: Meretrix Meretrix Linnaeussupporting
confidence: 78%
“…Until recently, in most centres, the standard initial induction chemotherapy for patients younger than 60-65 years with newly diagnosed acute myeloid leukaemia (AML) consisted of 7 d of cytarabine at 100-200 mg/m 2 /d and 3 d of daunorubicin at 45-50 mg/m 2 /d, the so-called '7&3' regimen (Yates et al, 1982;Dillman et al, 1991). However, in an attempt to improve response rates, various approaches have been explored, predominantly the intensification of this standard regimen, including the use of alternative anthracyclines (Berman et al, 1991;Mandelli et al, 1991;Vogler et al, 1992;Wiernik et al, 1992), increased doses of daunorubicin (Fernandez et al, 2009;Lowenberg et al, 2009), addition of third drugs, such as etoposide (Bishop et al, 1990), and increasing the dose of cytarabine (Mayer et al, 1994;Bishop et al, 1996;Weick et al, 1996;Buchner et al, 1999;Estey et al, 2001).…”
mentioning
confidence: 99%
“…Longer treatment with ara-C ("3ϩ10") does not induce higher remission rates, but the ''3ϩ7'' and ''3ϩ10'' regimens reportedly are more effective than less intensive regimens. [1][2][3][4] In recent years, three large randomized trials, including idarubicin in the induction regimen, produced significantly higher CR rates and prolonged survival compared with daunorubicin (55-60% and 69 -80%). [5][6][7] A metaanalysis of such studies suggested that idarubicin is associated with high CR rates and prolonged survival.…”
mentioning
confidence: 99%